Knowledge management and Parliament Content Management System - Sinyegwe, Azwinndini Phillys (My University, 2015)
The Globalisation of business, the shift from production-based to a knowledge-based economy, the growth of information communication technology (ICT), the strive to become learning organizations and the emergence of the need for knowledge workers have made Knowledge Management (KM) practice a must across all types and levels of organizations today (Chong, 2005). Organizations manage knowledge because if they do not, it has detrimental effects especially when employees leave organizations. Du Plessis (2005) indicates that when employees leave organizations they are likely to leave with valuable organizational knowledge. Successful KM has significant benefits for organizations. It enables organizations to harness this resource and continue to benefit from it even when employees have left the organizations. To successfully implement KM initiatives, an organization must take heed of KM success factors because absences of these factors lead to failure of KM initiatives. The purpose of this research is to explore the factors that are driving or impeding the effective implementation of the Parliament Content Management System (PCMS), as a KM initiative in the Parliament of the Republic of South Africa. The study has found that if leadership is not fully committed on the KM issues, KM initiatives will hardly succeed in an organization as it is the leadership‟s responsibility to come up with the KM implementation strategies; they have to ensure that employees are motivated and that there is a culture of knowledge sharing in the organization. The thesis consists of five chapters. Chapter 1 deals with the background of the study, introduction to the problem and the relevance of the study. Chapter 2 reviews literature on push factors for successful implementation of knowledge management initiatives. Chapter 3 discusses the research methodology. Chapter 4 analyses the data. Finally, chapter 5 deals with the conclusion of the study with a number of v recommendations to assist LOD in ensuring that PCMS, as a KM initiative achieves its intended objectives.
Thesis (M.M. (Public and Development Management))--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Governance, 2014.